2004
DOI: 10.1093/geronb/59.5.p203
|View full text |Cite
|
Sign up to set email alerts
|

Change in Object Naming Ability During Adulthood

Abstract: Using longitudinal data on the Boston Naming Test ( Kaplan, Goodglass, & Weintraub, 1983) collected over 20 years from healthy individuals aged 30 to 94, we examined change in lexical retrieval with age, gender, education, and their interactions. We compared results between random-effects longitudinal and traditional cross-sectional models. Random-effects modeling revealed significant linear and quadratic change in lexical retrieval with age; it also showed a Gender x Education interaction, indicating poorest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
3
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 37 publications
10
99
3
7
Order By: Relevance
“…These difficulties have been confirmed in many studies showing a word naming decline on the Boston Naming Test (BNT), both cross-sectional (e.g., MacKay, Connor, Albert, & Obler, 2002;Mariën, Mampaey, Vervaet, Saerens, & De Deyn, 1998) and longitudinal (Au et al, 1995;Barresi, Nicholas, Connor, Obler, & Albert, 2000;Connor, Spiro, Obler, & Albert, 2004;Goral, Spiro, Albert, Obler, & Connor, 2007).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…These difficulties have been confirmed in many studies showing a word naming decline on the Boston Naming Test (BNT), both cross-sectional (e.g., MacKay, Connor, Albert, & Obler, 2002;Mariën, Mampaey, Vervaet, Saerens, & De Deyn, 1998) and longitudinal (Au et al, 1995;Barresi, Nicholas, Connor, Obler, & Albert, 2000;Connor, Spiro, Obler, & Albert, 2004;Goral, Spiro, Albert, Obler, & Connor, 2007).…”
Section: Introductionmentioning
confidence: 84%
“…In participants in their 50s, this weakness may remain subtle; these participants may be able to activate the word, but do so more slowly than before. As Connor et al (2004) pointed out, the age-related decline in naming may accelerate with increasing age. In participants in their 60s, connections may have further weakened, leading to a decrease in the mean number of correct responses and slower correct naming latencies.…”
Section: Effects Of Aging On Naming Capacities: Age Of Onset and Theomentioning
confidence: 99%
See 1 more Smart Citation
“…In the present paper, we build on work conducted by Connor et al (2004) to examine age-related change in multiple lexical-retrieval skills. Here, we employ multivariate techniques to compare and contrast performance on five lexical tests: two picture-naming tests, two list-generation tests, and a vocabulary test that does not require the retrieval of specific labels.…”
mentioning
confidence: 99%
“…Holtzer et al's (2008) results revealed that the mean of the 15-item abbreviated version of the BNT was 12.2 (81.1%) for the age group 70-79 years and 11.6 (77.3%) for the age group 80-89 years, indicating a declining rate of approximately 0.5% per year. Perhaps the smallest decline rates reported thus far may be found in the longitudinal research by Connor et al (2004), who gave the BNT to people aged 30-80 years. The decline rates reported there are around 0.2% per year.…”
Section: Discussionmentioning
confidence: 91%